Efficacy of non-surgical treatments for acute non-specific low back pain: protocol for systematic review and network meta-analysis of randomised controlled trials - Geronimo Bejarano; Robert J Trager; Anthony N Baumann; Wren Burton; Elizabeth R Blackwood; Benjamin D Holmes; Christine M Goertz (BMJ Open)
Introduction Acute low back pain (LBP) is a prevalent condition with various non-surgical treatment options, yet no comprehensive network meta-analysis has systematically compared their relative efficacy for pain and disability. This study aims to fill that gap by synthesising available evidence on the efficacy of different types of non-surgical interventions for acute LBP, such as various medications, manual therapies and education-based therapies. Our coprimary objectives are to (1) compare each active treatment to an inert reference for measures of LBP and related disability and (2) rank the efficacy of treatments.Methods and analysis We will conduct a systematic search across multiple databases, including grey literature, to identify randomised controlled trials evaluating non-surgical treatments for acute LBP. Eligible studies must report on pain and/or disability outcomes in adults. The risk of bias will be assessed using the Risk of Bias tool, and the certainty of evidence will be graded using CINeMA (Confidence in Network Meta-Analysis). We will use a frequentist network meta-analysis to pool standardised mean differences in pain and disability, employing random-effects models to account for heterogeneity. A qualitative analysis will assess study characteristics and transitivity, while a quantitative analysis will evaluate efficacy and inconsistency. Results will be presented using network geometry, p-scores, forest plots, funnel plots, Egger’s test, Q-statistics and league tables to visualise both direct and indirect evidence and to identify potential biases.Ethics and dissemination This review protocol does not involve any primary research with human participants, animal subjects or medical record review. Consequently, this work did not require approval from an institutional review board or ethics committee. Results will be submitted to a peer-reviewed journal and presented at conference(s). De-identified data will be made available in a public repository.